REACTUALIZATION OF ISLAMIC CRIMINAL LAW VALUES IN THE BO' SANGAJI KAI MANUSCRIPT OF THE BIMA SULTANATE: A CONTENT ANALYSIS APPROACH - Muhammad Mutawali (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2025)
This article aims to explain the values of Islamic law contained in the Bo` Sangaji Kai manuscript. Bo` Sangaji Kai is a large book containing records of the kings of Bima and crucial information about the history of Bima, applicable laws and regulations, and diplomatic relations between the Bima kingdom and other kingdoms. It contains the genealogy of the kings of Bima. This study is library research by making the Bo` Sangaji Kai manuscript the primary source using a content analysis approach. This study found that in the Bo Sangaji Kai manuscript, it is explained in detail that the laws implemented by the Bima Sultanate are Islamic and customary. The results of the study in this article also confirm that the values of Islamic law are used as one of the sources of law used by the Bima Sultanate to resolve conflicts and legal problems faced by the Bima community, as revealed in several legal issues such as theft, adultery, and murder.